Cognitive Meaning of Inclusive Education of Students with Disability in Regular Education Teachers - Morales-Martínez, Guadalupe Elizabeth; Mezquita-Hoyos, Yanko Norberto; Castro-Campos, Claudia (Journal of Intellectual Disability - Diagnosis and Treatment, 2022)
Background: Successful inclusive education strongly represents the development of society, promoting better living conditions for students with disabilities. Objective: This study explored the mental representation of knowledge of inclusive education and disability held by regular education teachers with experience in this field. Methods: First, participants performed a conceptual definition task through the Natural Semantic Networks technique. Teachers defined ten target concepts related to the cognitive schema of inclusive education. They had 60 seconds to define each target, using verbs, adjectives, nouns, and pronouns, after rating the definers’ quality to conceptualize the target. Subsequently, the authors implemented a constraint satisfaction neural network to simulate the school inclusion schema's behavior and carried out a chronometric cognitive analysis using data from the first study. Results: Participants organized the educative inclusion meaning on four dimensions (definition, actors' qualities, stakeholders, and inclusion program effects). However, some concepts about school integration and conventional education appeared in the educative inclusion schema. Further, computer simulations showed that participants seem to have an internal locus of control over inclusive actions. Generally, experience with students with disabilities promotes the formation of a favorable educational inclusion schema. However, even though participants in this study have experience in inclusion programs, they are still constructing the inclusive education schema. Conclusion: The cognitive evaluation provides useful information to empower teachers to be aware of their knowledge and biases on inclusive education and the importance of their work in the success of school inclusion programs.